SFDRS as a metalanguage for ‘foodscaping’: adding a formal dimension to an interdisciplinary, multimodal approach to food - Kim, Loli; Calway, Niamh (Frontiers in Communication, 2024)
“Foodscaping” (MacKendrick, 2014) is set apart from the average study on food communication, even from “culinary linguistics'' (Gerhardt, Frobenius, Ley et al.2013) which is indeed multimodal and considers food and language to be both parallel and inherent to one another (Kiaer, Kim, and Calway, 2024 forthcoming). Foodscaping actively and evenly draws from expertise across all disciplines and modalities relevant to the discussion of a given food environment rather than providing siloed disciplinary analyses (Calway, Kim, and Winstanley- Chesters, 2026 forthcoming). However, like most interpretive analysis, researchers must interpret food environments that are not ‘local’ to them (Kim, 2022). The issue of cross-cultural differences in the production of analysis here is a pertinent one: how can personal interpretation be divorced from locally salient and meaningful discourses? This chapter will present the findings of a pilot analysis using the box notation style of Kim’s (2022) Korean Segmented Film Discourse Analysis (K-SFDRS), the finer-grain of a formal method of transcription developed for South Korean multimodal film discourse analysis, to analyse a spontaneous and authentic South Korean foodscaping experience. This pilot develops these “logical forms of discourse” by hierarchising them in what we term “cluster structures'', which correspond more effectively with spontaneous multimodal discourse analysis, due to the absence of cinematic editing that K- SFDRS is significantly informed by. We also examine the knowledge sources from which multimodality is linked to disciplines in order to direct the foodscaping analysis, due to the role the activation of knowledge about the world plays in the interpretation process (Wildfeuer, 2014), and which is fundamental not only in cross-cultural analysis but in ensuring the best disciplinary routes are found in research of foodscapes. The pilot will provide formality in transcription in the aims of ascertaining whether SFDRS could be used to productively support the analysis of a foodscape in this respect. Through this culinary scope, this chapter adds a new disciplinary dimension to discussions of metalanguage and makes an innovative contribution to the current corpus of multimodal research.